Exposure to tobacco marketing in bars predicts subsequent use of multiple tobacco products among non-tobacco-using college students. Issue 6 (10th December 2019) - Herrera, Ana Laura; Pasch, Keryn E; Marti, C Nathan; Loukas, Alexandra; Perry, Cheryl
Abstract : Background: Due to other marketing restrictions, one venue where tobacco companies concentrate their marketing efforts to reach young adults is bars/nightclubs. Objective: This study examined the relationship between exposure to tobacco marketing in bars/nightclubs and number of alternative tobacco/nicotine products used 6 months later among college students. Methods: Participants were 1, 406 students aged 18–29 years old who reported going to bars or nightclubs at least rarely (M age=21.95; 67% female; 46% non-Hispanic white). Students completed an online survey in fall 2014/spring 2015 (wave 1) and again 6 months later (wave 2). Multilevel Poisson regression models were used to assess the relationship between exposure to three types of marketing at bars/nightclubs at wave 1 (tobacco/nicotine product advertisements; free samples; industry representatives) and number of tobacco products used (range=0–5) at wave 2, controlling for school type (2 year vs 4 year), age, sex, race/ethnicity and frequency of bar visits. An interaction between the number of wave 1 products and each marketing variable was tested. Results: Greater exposure to free samples and tobacco industry representatives at bars/nightclubs predicted a greater number of products used 6 months later, but only among wave 1 non-tobacco users and not among tobacco users. Exposure to advertisements at bars/nightclubs did not predict the number of products used 6 months later. Conclusion: Tobacco companies claim that marketing is targeted to those who already use the product, not to non-users. However, the current study indicates tobacco marketing in bars and nightclubs may encourage use among non-users and has no influence on current users.